(E)-2-Methoxy-N′-(2,4,6-trihydroxybenzylidene)benzohydrazide - Taha, Muhammad (International Union of Crystallography, 2013)
In the title hydrazone derivative, C(15)H(14)N(2)O(5), the benzene rings are twisted by 7.55 (8)° with respect to each other. The azomethine double bond adopts an E conformation. The molecular structure is stabilized by intramolecular O—H⋯N and N—H⋯O hydrogen bonds, generating S6 ring motifs. In the crystal, molecules are linked into a three-dimensional network by O—H⋯O hydrogen bonds.